2007
DOI: 10.1074/jbc.m702477200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recombinant CDR1, an Arabidopsis Aspartic Proteinase Involved in Disease Resistance

Abstract: The Arabidopsis thaliana constitutive disease resistance 1 (CDR1) gene product is an aspartic proteinase that has been implicated in disease resistance signaling (Xia, Y., Suzuki, H., Borevitz, J., Blount, J., Guo, Z., Patel, K., Dixon, R. A., and Lamb, C. (2004) EMBO J. 23, 980 -988). This apoplastic enzyme is a member of the group of "atypical" plant aspartic proteinases. As for other enzymes of this subtype, CDR1 has remained elusive until recently as a result of its unusual properties and localization. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
0
35
0
3
Order By: Relevance
“…It has been shown that the plant-speciWc insert is removed entirely or partially during maturation and processing of plant AP precursor (Guruprasad et al 1994;Frazao et al 1999;White et al 1999). There are 69 genes encoding aspartyl proteases in the Arabidopsis genome (Takahashi et al 2008), and studies on their expression at the protein level as well as their physiologic roles have already started (Simoes et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the plant-speciWc insert is removed entirely or partially during maturation and processing of plant AP precursor (Guruprasad et al 1994;Frazao et al 1999;White et al 1999). There are 69 genes encoding aspartyl proteases in the Arabidopsis genome (Takahashi et al 2008), and studies on their expression at the protein level as well as their physiologic roles have already started (Simoes et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The gene product of A. thaliana constitutive disease resistance 1 (CDR1) is an apoplastic aspartic protease and is a member of a larger group of the atypical aspartic protease (Simões et al, 2007). The overexpression of CDR1 causes dwarfing and resistance to virulent P. syringae, and the suppression of CDR1 results in compromised resistance to avirulent P. syringae and in increased susceptibility to virulent strains compared to the wild type.…”
Section: Roles Of Plant Non-proteasomal Proteases In Pathogen Defensementioning
confidence: 99%
“…Another Arabidopsis aspartic protease, PROMOTION OF CELL SURVIVAL1 (PCS1), has an anti-cell death role in embryonic and reproductive development 32 . A third Arabidopsis aspartic protease, CONSTITUTIVE DISEASE RESISTANCE 1 (CDR1) is associated with signalling in disease resistance 33 . S5 is the only characterized aspartic protease from rice; its gene is a major locus for indica-japonica hybrid sterility 34 .…”
mentioning
confidence: 99%